Incentivizing improvement or imposition? An examination of the response to gubernatorial school takeover and statewide turnaround districts - Welsh, Richard O.; Williams, Sheneka M. (Education Policy Analysis Archives, 2018)
Although state-run school districts and gubernatorial school takeover have become popular turnaround strategies among some states, little is known about how district and school leaders perceive and respond to these changes in educational governance. Using Georgia as a case study, this paper employs sensemaking and exit, voice, and loyalty as frameworks to examine how district and school leaders interpret and respond to the threat of state takeover. Similar to prior studies, results indicate that urban schools and districts largely populated by low-income students and students of color are most likely to be affected by state takeover. Several themes emerge from district and school leaders’ interpretation of state takeover policy, including: (a) principals and teachers are to blame, (b) too many changes, too little time to reflect, (c) lack of trust between school districts and the state, and (d) market-based reforms and the illusion of choice. Although a non-trivial number of teachers and principals have expressed their intent to leave for charter schools or leave the teaching profession in response to the threat of state takeover, voice was the more common response, particularly among teachers in takeover-eligible schools who were more experienced and had students performing well on state tests. There are also noteworthy differences in the response of district and school leaders based on the eligibility for state takeover.